The Effect of Biofloc with the Addition of Different Commercial Probiotics in Catfish (Clarias sp.) - Dewi Putri Lestari; Fariq Azhar; Muhammad Marzuki (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Catfish was one of the most popular consumption fish in Indonesia. Increasing the production of catfish farming by means of super intensive cultivation has a negative impact on the quality of the aquaculture environment which in turn can have an impact on fish health. Biofloc technology was an alternative that can be done to solve the problem of aquaculture waste. In fact, it could provide more benefits because besides being able to reduce inorganic nitrogen waste ÃÂ also provide additional feed for cultured fish so that it can increase growth and feed efficiency. This study aims to evaluate the growth performance of catfish (Clariassp.) In biofloc-based super intensive cultivation with the addition of different commercial probiotics. This research will be conducted for 5 months. The research was conducted in an aquarium in the form of an aquarium measuring 90 Ãâ 40 Ãâ 50 cm filled with 100 L. The treatment given was the addition of commercial probiotics in the culture medium with the biofloc system and fermented pellet feed with various commercial probiotics, namely commercial probiotic I, commercial probiotic II. , commercial probiotic III, positive control (biofloc culture media and without the addition of commercial probiotics), and negative control (without biofloc). Each treatment was repeated three times. Specific data growth, survival (SR), feed conversion ratio (FCR) and quality were statistical analysis with one-way analysis of variance. The results showed that the best growth performance of catfish using the biofloc culture system produced in this study was shown in PK3 treatment with a survival rate of 93.33%, a specific growth rate of 6.60, and a feed conversion ratio of 0.92.ÃÂ